Effects of NaOCl or Combination of NaOCl and Various Acids on Dentin Surface Morphology: A SEM Study - Gökçe Kağan; Benderli Yasemin; Kazak Mağrur (Balkan Stomatological Society, 2014)
The aim of this study was to evaluate by SEM morphological changes of dentin surfaces under the use of 5% NaOCl before applying different acids for etching. In the study, dentin surfaces were prepared from the middle third of 20 non-carious human third molars. Samples were divided into 2 groups with 3 subgroups each. In the first group, no application was performed on dentin surfaces. In the second group, 5% NaOCl was applied for 60 seconds on the dentin surfaces then rinsed with distilled water for 5 seconds. In all of the subgroups, dentin surfaces were etched by different conditioning agents for 15 seconds then rinsed for 30 seconds. After surface applications, all of the specimens were placed in distilled water. Morphological changes of dentin surfaces were determined by SEM. The results were evaluated by the scoring system based on Brannström et al.